Imidazolium‐Based Poly(Ionic Liquid)s Featuring Acetate Counter Anions: Thermally Latent and Recyclable Precursors of Polymer‐Supported N‐Heterocyclic Carbenes for Organocatalysis. Issue 14 (18th March 2016) - Lambert, Romain; Coupillaud, Paul; Wirotius, Anne‐Laure; Vignolle, Joan; Taton, Daniel
Abstract : Statistical copoly(ionic liquid)s (coPILs), namely, poly(styrene)‐ co ‐poly(4‐vinylbenzylethylimidazolium acetate) are synthesized by free‐radical copolymerization in methanolic solution. These coPILs serve to in situ generate polymer‐supported N ‐heterocyclic carbenes (NHCs), referred to as polyNHCs, due to the noninnocent role of the weakly basic acetate counter‐anion interacting with the proton in C2‐position of pendant imidazolium rings. Formation of polyNHCs is first evidenced through the quantitative formation of NHC‐CS2 units by chemical postmodification of acetate‐containing coPILs, in the presence of CS2 as electrophilic reagent (= stoichiometric functionalization of polyNHCs). The same coPILs are also employed as masked precursors of polyNHCs in organocatalyzed reactions, including a one‐pot two‐step sequential reaction involving benzoin condensation followed by addition of methyl acrylate, cyanosilylation, and transesterification reactions. The catalytic activity can be switched on and off successively upon thermal activation, thanks to the deprotonation/reprotonation equilibrium in C2‐position. NHC species are thus in situ released upon heating at 80 °C (deprotonation), while regeneration of the coPIL precursor occurs at room temperature (reprotonation), triggering its precipitation in tetrahydrofuran. This also allows recycling the coPIL precatalyst by simple filtration, and reusing it for further catalytic cycles. The different organocatalyzed reactions tested can thus be performed with excellent yields after several cycles. Abstract : Statistical styrenic‐type copoly(ionic liquid)s based on imidazolium units and featuring weakly basic acetate counter‐anions behave as thermally latent and recyclable precursors of polymer‐supported N ‐heterocyclic carbenes for the purpose of organocatalysis.